Articulations of Islamic nationalism in the educational reform discourse of 'new Turkey'. Issue 2 (4th March 2022) - Sen, Abdulkerim
ABSTRACT: Turkey has become a powerful example of rising ethno-religious nationalism since the ruling Justice and Development Party allied with the Nationalist Movement Party in 2016. Conceptualising the political ideology in power as Islamic nationalism, I expose ways in which this ideology is articulated in the education reform discourse of 'new Turkey' through a critical analysis of a foundational education reform report (the Report). The analysis shows various aspects of ethno-religious construction of education reform discourse through a focus on citizenship education (CE) partly because the prominent configuration of power relations manifests itself in considerations of CE. The analysis finds that the Report vilifies CE and proposes an alternative for it: social entrepreneurship. Furthermore, it presents Turkey's diverse population as a monolithic homogenous mass and makes no mention of democracy and human rights values. These findings call out the research community to investigate the negative implications of rising ultra-nationalism for CE.